SEMUT IDE DALAM KARYA SENI GRAFIS - FIRMANSYAH, Yofita Sandra, S.Pd., M.Pd. Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2018)
The purpose of work is to visualize the object of ants into works of art with graphics screen-printed technique (serigraphy). Create a masterpiece there are several stages: Preparation (tools and materials), phase of elaboration, sistensis, realization of the concept, and settlement. Several stages in the process of creating ten works of art have finished.This final paper more describing about appropriate behaviour and activity of many leading to human life from the way ants living a lot applying the behavior and social attitudes among them. Visual form of packaged with the title: sharing, Not easily surrender, discipline, teamwork, trying, admonished the sapa, helping without being asked, the hard work, work for the common good, care.Key words: ants, ideas, graphics